Debating the end of Yugoslavia - Bieber, Florian; Galijaš, Armina; Archer, Rory (Southeast European Studies 5, 2014)
Debating the End of Yugoslavia is less an attempt to re-write the dissolution of Yugoslavia, or to provide a different narrative, than to take stock and reflect on the scholarship to date. New sources and data offer fresh avenues of research avoiding the passion of the moment that often characterized research published during the wars and provide contemporary perspectives on the dissolution. The book outlines the state of the debate rather than focusing on controversies alone and maps how different scholarly communities have reflected on the dissolution of the country, what arguments remain op